Local court, provincial society, and justice in the Ottoman Empire : legal practice and dispute resolution in Çankırı and Kastamonu (1652-1744) - Ergene, Boğaç A., 1971- (Studies in Islamic law and society, 2003)
This work covers the functions of Islamic courts within the framework of the late 17th- and early 18th-century Ottoman provincial administration, and explores the process of adjudication and dispute resolution through a juxtaposition of court records from two Anatolian towns, Cankiri and Kastamonu.